Does the Physiotherapist Know the ideal moment to start NIV and when to Know if the intervention in Covid-19 has failed? (Research, Society and Development, 2022)
Introduction: With the high rate of Covid-19 and many respiratory discomforts such as hypoxemia and symptomatological predictors, the most favorable moment to intervene with NIV treatment is instigated. Objective: Does the physical therapist know when to intervene with NIV in Covid-19; How to know if NIV has failed. Methodology: This study was characterized by a literature review guided by the search in the databases: Pedro, Scielo, Lilacs and PubMed. Conclusion: NIV proved to be effective as a treatment for Covid-19 in individuals who have mild to moderate, therefore not severe, respiratory distress and who have a positive test from 30 min to 2 hours of NIV with significant improvement.